2010
DOI: 10.2146/ajhp090572
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative venous thromboembolism on Medicare recipients undergoing total hip replacement or total knee replacement surgery

Abstract: Patients who developed VTE after THR or TKR had a higher likelihood of mortality, bleeding, and rehospitalization; were hospitalized longer; and incurred higher costs to Medicare, Medicare beneficiaries, and private payers compared with patients without VTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…More studies are needed of the costs of treating VTE in specific patient groups such as major orthopedic surgical patients [76] and pediatric patients [77]. One study reported that the total cost of care during the first 6 months post-discharge from orthopedic surgery was $3500 [78], whereas another study reported that the monthly cost during the first 3 months was $3300 higher than for matched controls [79].…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed of the costs of treating VTE in specific patient groups such as major orthopedic surgical patients [76] and pediatric patients [77]. One study reported that the total cost of care during the first 6 months post-discharge from orthopedic surgery was $3500 [78], whereas another study reported that the monthly cost during the first 3 months was $3300 higher than for matched controls [79].…”
Section: Discussionmentioning
confidence: 99%
“…For outpatient events, we developed a pilot NLP system to identify clinical notes with mentions of PE, DVT, or VTE [2325]. Each mention was associated with the date the clinic note was created.…”
Section: Methodsmentioning
confidence: 99%
“…Since most shoulder arthroplasties are elective, it is important to estimate how commonly serious postoperative complications such as cardiac and thromboembolic complications occur and what factors are associated with them. Cardiac and thromboembolic complications are associated with significantly higher morbidity and mortality in arthroplasty patients (3)(4, 5). A better understanding of these potentially fatal complications after shoulder arthroplasty will allow both surgeons and patients to make better informed decisions regarding this elective procedure.…”
mentioning
confidence: 99%